Price stabilization as a bonding mechanism in new equity issues - Benveniste, Lawrence M.; Busaba, Walid Y.; Wilhelm, William J. (Journal of Financial Economics, 1996)
Underwriters have an incentive to overstate investor interest in order to persuade some investors to purchase shares at a price in excess of their initial estimate of the fair value. We show that this incentive is eliminated when the underwriter commits to secondary market price stabilization. Destroying the underwriter's incentive to overstate interest reduces the total surplus captured by initial investors in initial public offerings. Further efficiency gains are associated with penalty bid systems that permit the underwriter to make the stabilization commitment selectively. Price stabilization can thus be viewed as a bonding mechanism that improves the efficiency of the primary equity market.